PENGARUH FDR TERHADAP ROA DENGAN VARIABEL INTERVENING NPF PADA BPRS INDONESIA 2011-2016 - Arif Maulana; Noven Suprayogi (Universitas Airlangga, 2019)
This research aims to know the influence of Financing to Deposit Ratio (FDR) against Non Performing Financing (NPF), the influence of Non-Performing Financing (NPF) towards profitability, leverage Financing to Deposit Ratio (FDR) towards profitability , on the Bank of the people's Islamic Financing in Indonesia. The approach used is the quantitative approach using path analysis or path analysis. The sample used in this study is the BPRS from January 2011 to December 2016. The data is drawn from Islamic Banking Statistics issued by Bank Indonesia and the financial services authority totalling 72 data. The results of this study showed that Non Performing Financing (NPF) and the Financing to Deposit Ratio (FDR) influential negative and significantly to Profitability (RoA). Non Performing Financing (NPF) a positive effect towards Profitability (RoA) Keywords: NPF, FDR, ROA, InterveningREFERENCES Afif, Z. N. (2014). Pengaruh Pembiayaan Murabahah Terhadap Laba Melalui Variabel Intervening Pembiayaan Bermasalah Bank Umum Syariah di Indonesia Periode 2009-2013. (Skripsi S1), Fakultas Ekonomi dan Bisnis Universitas AirlanggaIndriantoro, Nur., dan Supomo, Bambang. (2013). Metodologi Penelitian Bisnis Untuk Akuntansi & Manajemen. Yogyakarta: BPFEMuhammad. (2004). Manajemen Dana Bank Syariah. Yogyakarta: Jalasutra.Mukti, Nur Abidah. (2016). Pengaruh BOPO dan FDR Terhadap Profitabilitas BPR Syariah dengan Risiko Pembiayaan Sebagai Variabel Intervening (Studi Empiris Pada Bank Pembiayaan Rakyat Syariah Provinsi DKI Jakarta, Jawa Barat dan Banten yang terdaftar di Bank Indonesia Periode 2012-2015). (Skripsi S1), Fakultas Ekonomi dan Bisnis Universitas JemberPurbaningsih, Y. P. (2014). The Effect of Liquidity Risk and Non Performing Financing (NPF) Ratio to Commercial Sharia Bank Profitability in Indonesia. International Proceedings of Economics Development and Research(Online), Vol. 73, 12.Republik Indonesia. Undang-Undang Nomor 21 Tahun 2008 Tentang Perbankan Syariah. 2008, (Online), (www.ojk.go.id, diakses 22 Maret 2017)———-. Statistik Perbankan Syariah, Januari 2011-Desember 2016. 2011-2016, (Online), (www.ojk.go.id, diakses 22 Maret 2017———-. Undang-Undang Tentang Perbankan dan Peraturan Pemerintah Nomor 72 Tahun 1992. 19992, (Online), (www.ojk.go.id, diakses 22 Maret 2017)Sabir, dkk. (2012). Pengaruh Rasio Kesehatan Bank Terhadap Kinerja Keuangan Bank Umum Syariah dan Bank Konvensional di Indonesia. Jurnal Analisis, Vol. 1(No. 1).Sukarno, & Syaichu. (2006). Analisis Faktor-Faktor yang Mempengaruhi Kinerja Bank Umum di Indonesia. Jurnal Studi Manajemen & Organisasi UNDIP, Vol. 3(Nomor 2).Wibowo. (2013). Analisis Pengaruh Suku Bunga, Inflasi, CAR, BOPO, NPF, Terhadap Profitabilitas Bank Syariah. Jurnal Manajemen UNDIP, Vol. 2(No. 2).